Prevalence of Irritable Bowel Syndrome (IBS) in Lamar- Libya Primary Care General practices - Awami, Salem; Alhomry, Faraj; Mohamed, Najib (Al-Mukhtar Journal of Sciences, 2018)
Irritable bowel syndrome (IBS) is a chronic or recurrent abdominal symptom. No cause can be identified using conventional diagnostic testing and it is characterized by abdominal pain or cramping and changes in bowel function. Aims of our study were to estimate the prevalence of functional bowel disorders namely C1; Irritable bowel syndrome (IBS) among clinic-based patients, and to assess health-care seeking in subjects with functional bowel disorders. The study used participants recruited from AL Marj- Libyan Red Crescent Clinic primary care general practices. Between November 2012 and December 2013, each study subject was asked according to a prepared questionnaire. This questionnaire depends on Rome III diagnostic criteria for irritable bowel syndrome.  450 consecutive patients attended the Red Crescent Clinic, 234 (52%) were female and 216 (48 %) were male. Population age ranged from 20-80 years, and the mean age was 53 years (SD+ 15.6). In our study, the prevalence of irritable bowel syndrome (IBS) is 12%, and 53.3% of the subjects had looked for medical advice for abdominal pain. There was no significant association observed between the prevalence of IBS and sex. IBS was11.9% in women and 12.1% in men. Elderly were the least frequent sufferer of IBS and the least medical advice seeker compared to younger age groups, which necessitate not overlooking organic cause in such age group. Considerable patients seek medication and traditional remedies due to their bowel disorders. Further investigations of the treatment are required because of the high financial burden for individuals as well as for the society.